Antiviral defense in salmonids – Mission made possible?. Issue 87 (April 2019) - Dahle, Maria K.; Jørgensen, Jorunn B.
Abstract: Viral diseases represent one of the major threats for salmonid aquaculture. Survival from viral infections are highly dependent on host innate antiviral immune defense, where interferons are of crucial importance. Neutralizing antibodies and T cell effector mechanisms mediate long-term antiviral protection. Despite an immune cell repertoire comparable to higher vertebrates, farmed fish often fail to mount optimal antiviral protection. In the quest to multiply and spread, viruses utilize a variety of strategies to evade or escape the host immune system. Understanding the specific interplay between viruses and host immunity at depth is crucial for developing successful vaccination and treatment strategies in mammals. However, this knowledge base is still limited for pathogenic fish viruses. Here, we have focused on five RNA viruses with major impact on salmonid aquaculture: Salmonid alphavirus, Infectious salmon anemia virus, Infectious pancreatic necrosis virus, Piscine orthoreovirus and Piscine myocarditis virus. This review explore the protective immune responses that salmonids mount to these viruses and the existing knowledge on how the viruses counteract and/or bypass the immune response, including their IFN antagonizing effects and their mechanisms to establish persisting infections. Highlights: Viruses use a variety of strategies to evade or escape the host immune system. Most viruses suppress the immune system by IFN antagonism. T cell mediated immunity against viruses needs to be better characterized. Some viruses avoid immune detection and develop persistence. The role of red blood cells in the salmonid immune system is a new field to explore.